Prognostic Value of Neutrophil-to-Lymphocyte Ratio and Vaccination for Negative Conversion Time of Nucleic Acid in Nonsevere COVID-19 Patients Infected by SARS-CoV-2 Omicron Variant - Kongbo Zhu; Shaolei Ma; Hui Chen; Jianfeng Xie; Dan Huang; Zhenghua Hou; Shanhu Qiu; Genshan Ma; Yingzi Huang (International Journal of Clinical Practice)
SARS-CoV-2 Omicron variant is significantly different from all the previous variants and has rapidly replaced other variants as the dominant variant across the globe. An easily obtained, inexpensive, and rapid marker is needed to predict the negative conversion time (NCT) of nucleic acid in nonsevere COVID-19 patients infected by the Omicron variant. This retrospective study enrolled 226 patients infected by the Omicron variant between April 23, 2022, and May 16, 2022. The median age of the patients was 61 (interquartile range (IQR), 48–70) years, and 56.2% were male. 84 patients (37.2%) had at least one comorbidity, and 49 patients (21.7%) were classified into the moderate illness group. 145 patients (64.2%) received at least one dose of vaccine, in which 67 patients (29.6%) received a booster dose of vaccine. The median duration of NCT was 8 (IQR, 7–11) days. Univariate Cox analyses found that high NLR (>2.22), aged ≥65 years, vaccination, and moderate illness were significantly related to the NCT of nucleic acid. Multivariate Cox regression analysis showed that high NLR (NLR > 2.22, hazard ratio (HR):0.718, 95% CI: 0.534–0.964, p = 0.028) and vaccination (vaccinated ≥1 dose, HR: 1.536, 95% CI: 1.147–2.058, p = 0.004) were independently associated with NCT of nucleic acid. NLR is a rapid, simple, and useful prognostic factor for predicting NCT of nucleic acid in nonsevere COVID-19 patients with the Omicron variant. In addition, vaccination may also play a valuable role in predicting the NCT of nucleic acid.